2006
DOI: 10.1038/sj.emboj.7601378
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin-1 mediates large pore formation and interleukin-1β release by the ATP-gated P2X7 receptor

Abstract: P2X 7 receptors are ATP-gated cation channels; their activation in macrophage also leads to rapid opening of a membrane pore permeable to dyes such as ethidium, and to release of the pro-inflammatory cytokine, interleukin-1b (IL-1b). It has not been known what this dye-uptake path is, or whether it is involved in downstream signalling to IL-1b release. Here, we identify pannexin-1, a recently described mammalian protein that functions as a hemichannel when ectopically expressed, as this dye-uptake pathway and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
1,484
18
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,274 publications
(1,592 citation statements)
references
References 48 publications
53
1,484
18
3
Order By: Relevance
“…The P2X7 receptor has been reported to interact with the channel protein pannexin 1 [32], and this complex creates a sizeable pore permeable to larger molecules such as ethidium bromide [33]. To assess the effect of pannexin1 on ETX-induced hemolysis, carbenoxolone and mefloquine were used as antagonists for pannexin 1.…”
Section: Resultsmentioning
confidence: 99%
“…The P2X7 receptor has been reported to interact with the channel protein pannexin 1 [32], and this complex creates a sizeable pore permeable to larger molecules such as ethidium bromide [33]. To assess the effect of pannexin1 on ETX-induced hemolysis, carbenoxolone and mefloquine were used as antagonists for pannexin 1.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced intracellular K þ concentration is the primary trigger of caspase-1 activation (Munoz-Planillo et al, 2013). While some reports indicate that Panx1 channel opening is an obligatory part of both NLRP1 and NLRP3 inflammasome activation (de Rivero Vaccari et al, 2008;Pelegrin and Surprenant, 2006;Silverman et al, 2009), other groups have reported P2X7 receptor-induced IL-1b release, independent of Panx1 (Pelegrin et al, 2008;Qu et al, 2011). A further study postulated that Panx1 is responsible for the release of ATP from dying cells, upstream of P2X7 activation in the signaling cascade (Dahl and Keane, 2012).…”
Section: The Role Of P2x Receptors In Neuroinflammationmentioning
confidence: 99%
“…Current inhibition curves indicated IC 50 of 16.3±2.1 nM (n ¼ 3-9 cells) and 9.8±0.9 nM (n ¼ 2-9 cells) for KN62 and A740003, respectively (Figure 2d), which are the classical concentrations used for antagonizing hP2X 7 R activity (Donnelly-Roberts and Jarvis, 2007). Sustained activation of P2X 7 R is also known to induce membrane permeation following the activation of pannexin-1 and allowing the uptake of membrane-impermeant fluorescent dyes such as ethidium (Pelegrin and Surprenant, 2006). Ethidium uptake was also recorded in MDA-MB-435s cells stimulated with ATP (5mM), which was completely inhibited when KN62 (1 mM) was added to the external solution (Figure 2e).…”
Section: Human Cancer Cells Express Functional P2x 7 Rmentioning
confidence: 99%
“…PCR products were then analyzed by electrophoresis in 1% agarose gel containing ethidium bromide, and visualized by UV transillumination. Detailed methods used for qRT-PCR have been described previously (Pelegrin and Surprenant, 2006). Specific primers were purchased from Qiagen (QuantiTech Primer Assays), for each primer set the efficiency was 495% and a single product was seen on melt curve analysis.…”
Section: Reverse Transcription Pcr (Rt-pcr) and Quantitative Rt-pcr Amentioning
confidence: 99%
See 1 more Smart Citation